2017
DOI: 10.4238/gmr16019272
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive role of Kruppel-like factor 4 (KLF-4) in colorectal cancer

Abstract: ABSTRACT. Kruppel-like factors (KLFs) are a group of transcriptional regulators that have recently been identified to exhibit tumorsuppressive function against various gastrointestinal cancers. The present study aims to investigate the expression patterns and prognostic value of KLF-4 in colorectal cancers (CRCs). KLF-4 levels in CRC tissues were examined via immunohistochemistry analysis, real-time quantitative polymerase chain reaction, and western blotting. The chisquare test was performed to evaluate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…KLF4 is a conserved zinc finger-containing transcription factor that regulates multiple biological processes [24]. Recently, researchers found that KLF4 acts as a tumor suppressor in various human cancers, such as colorectal cancer, ovarian cancer, HCC, and lung cancer [[25], [26], [27], [28]]. Overexpression of KLF4 recovers cyclin dependent kinase inhibitor 1B (KIP1) protein expression, a negative regulator of the cell cycle, and suppresses the epithelial-mesenchymal transition (EMT) protein, snail family transcriptional repressor 2 (SNAI2) in HCC cells [11].…”
Section: Resultsmentioning
confidence: 99%
“…KLF4 is a conserved zinc finger-containing transcription factor that regulates multiple biological processes [24]. Recently, researchers found that KLF4 acts as a tumor suppressor in various human cancers, such as colorectal cancer, ovarian cancer, HCC, and lung cancer [[25], [26], [27], [28]]. Overexpression of KLF4 recovers cyclin dependent kinase inhibitor 1B (KIP1) protein expression, a negative regulator of the cell cycle, and suppresses the epithelial-mesenchymal transition (EMT) protein, snail family transcriptional repressor 2 (SNAI2) in HCC cells [11].…”
Section: Resultsmentioning
confidence: 99%
“…KLF4 has a reciprocal regulatory relationship with TGF-β1 and thus affects EMT ( 84 , 87 ). Colorectal cancer specimens with malignant features such as lymphatic metastasis showed low expression of KLF4 ( 156 ). Further studies revealed that KLF4 was negatively correlated with EMT indicators such as TWIST, β-catenin, claudin-1, N-cadherin, and vimentin, implying disrupted intestinal epithelial homeostasis, loss of cell polarity and intercellular junctions ( 157 ).…”
Section: Implications Of Klfs In Tumor Developmentmentioning
confidence: 99%
“…The broadly described role of KLF4 in colorectal cancer (CRC) remains controversial. Many studies have shown that KLF4 plays a tumor-suppressive role in CRC [ 3 ]. The reduced expression of KLF4 in human CRC tissues has been associated with increased growth of CRC cells, lymphatic node metastasis, reduced tumor cell differentiation, and tumor recurrence.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…CRC patients with lymph node metastasis display reduced KLF4 expression. Furthermore, the downregulation of KLF4 is associated with poor prognosis in human CRC patients, decreased overall survival as well as disease-free survival [ 3 ].…”
Section: Colorectal Cancermentioning
confidence: 99%